ASPECTS DEFINITION OF RELIABILITY EVALUATION FACADE SYSTEMS FROM THE VIEW POINT OF EUROCODE - Radkevych, A. V.; Netesa, K. M. (Science and Transport Progress, 2015)
Purpose. This paper is devoted to the definition of the most rational technique of reliability evaluation of facade systems of multistoried residential buildings with using the experience of buildings construction and operation abroad. The subject is also focused on defining the parameters of materials and facade systems, the improvement of which can increase the reliability and durability of facade systems of multistoried residential buildings, as well as cut the cost of their operation. Methodology. A comparative analysis of the operating experience of various types of facade systems in Ukraine and abroad based on the data of different authors was conducted. The analysis of the impact of external factors on facade systems with the subsequent comparison of methods for assessing the reliability of facades according to the criteria stated in the Eurocode was carried out as well as the selection of parameters that determine the reliability and durability of facade systems. Findings. Authors have performed researches of evaluation methods of organizational and technological reliability and durability of modern facade systems. It was identified the cause of the failure of facade systems. It is offered the ways of materials improvement of facade systems, and constructional and organization-technological decisions on the structure of facade systems. Methods of increase of reliability and durability of front systems were defined. Originality. The most rational technique of reliability evaluation of facade systems considering requirements of Eurocode in questions structural design was defined. Practical value. Improvement of evaluating methods for organizational-technological reliability of facade systems of multistoried residential buildings will predict more accurately the lifetime of enclosures. Using the methods described in the Eurocodes, to determine the reliability and durability of the facade systems will provide the general criteria for the building structures design in Ukraine and Europe, as well as facilitate the exchange of experience in the construction and operation of buildings between the countries of Europe. An analysis of the causes of failures of facades enables to determine the directions of improving the properties of the materials used for the manufacture of facade elements structures as well as engineering and technological solutions of applied facade systems.